Architecting a Floatable, Durable, and Scalable Steam Generator: Hydrophobic/Hydrophilic Bifunctional Structure for Solar Evaporation Enhancement. Issue 2 (19th September 2018) - Gao, Tingting; Li, Yiju; Chen, Chaoji; Yang, Zhi; Kuang, Yudi; Jia, Chao; Song, Jianwei; Hitz, Emily M.; Liu, Boyang; Huang, Hao; Yu, Jianyong; Yang, Bao; et al.
Abstract: Solar steam generation has been extensively investigated recently as a sustainable and environmentally friendly technology for water purification. Although various materials such as graphene and cellulose have been utilized for the construction of solar steam generators, high cost and inferior durability greatly hinder their practical application. In this work, a low‐cost, floatable, durable, and scalable evaporator is designed with an open nanofiber‐based bifunctional structure for high‐efficiency solar steam generation. The integrated bilayer evaporator is successively composed of electrospun hydrophobic polyvinylidene fluoride (PVDF) nanofibers and hydrophilic carbon black/polyacrylonitrile (CB/PAN) composite nanofiber layers from the bottom up. The porous hydrophobic PVDF nanofiber layer, due to their intrinsic low thermal conductivity, serves as the floating support and thermal barrier to suppress the irreversible heat dissipation. The hydrophilic CB/PAN composite nanofiber layer on the top has a high broadband solar adsorption of 98.6% from the wavelength of 250–2500 nm, which can effectively convert solar irradiation into available heat energy. The assembled CB/PAN//PVDF (CP/P) evaporator possesses an impressive solar energy conversion efficiency of 82.0% under one‐sun illumination and superior long‐term stability. The cost‐efficient polymer‐nanofiber‐based evaporator with excellent flexibility, durability, and scalability holds great promise in the practical application of water desalination and sterilization. Abstract : A low‐cost, floatable, durable, and scalable evaporator with an open nanofiber‐based bifunctional structure for high‐efficiency solar steam generation is designed using a facile electrospinning technique. The assembled flexible bilayer solar steam generator can achieve a high solar energy conversion efficiency under one‐sun illumination and demonstrates excellent long‐term stability and reusability.